2012
DOI: 10.1103/physrevb.86.134509
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle interference and the interplay between superconductivity and density wave order in the cuprates

Abstract: Scanning tunneling spectroscopy (STS) is a useful probe for studying the cuprates in the superconducting and pseudogap states. Here we present a theoretical study of the Z-map, defined as the ratio of the local density of states at positive and negative bias energies, which frequently is used to analyze STS data. We show how the evolution of the quasiparticle interference peaks in the Fourier transform Z-map can be understood by considering different types of impurity scatterers, as well as particle-hole asymm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…This model predicts the emergence of seven inequivalent dispersive peaks, which can be found by connecting points on the Fermi surface where the pairing gap is equivalent to the tip-sample voltage. As shown for example by Nowadnick et al 36 , these peaks are indeed reproduced by Eq. ( 13) in the limit of Γ → 0.…”
Section: B Stm: Dispersive Vs Non-dispersive Peakssupporting
confidence: 74%
“…This model predicts the emergence of seven inequivalent dispersive peaks, which can be found by connecting points on the Fermi surface where the pairing gap is equivalent to the tip-sample voltage. As shown for example by Nowadnick et al 36 , these peaks are indeed reproduced by Eq. ( 13) in the limit of Γ → 0.…”
Section: B Stm: Dispersive Vs Non-dispersive Peakssupporting
confidence: 74%
“…Specifically, our theory explains why (i) the x-ray-scattering signal is peaked at wave vector (q, 0), rather than at (q, q), as expected for CDWs; (ii) the RIXS signal is peaked at frequency = 0 and is accompanied by weaker dispersive inelastic peaks. Our findings also agree with earlier STS experiments of BSCCO [8][9][10], which found that the incommensurate checkerboard order has a dominant PDW character [72][73][74][75]. Attributing the x-ray signal to fluctuations of the pairing order parameter (PDW) explains its temperature dependence: these fluctuations are strongest at the critical temperature of superconducting order parameter, T c , in agreement with the experimental observations ( [12,16]).…”
supporting
confidence: 92%
“…Specifically, our theory explains why the experimental signal is peaked at (q, 0), rather than at (q, q), as expected for CDWs. Our findings also agree with earlier STS experiments of BSCCO [8][9][10], which found that the incommensurate checkerboard order has a dominant PDW character [68][69][70][71]. The proposed PDW scenario explains why the signal detected in X-ray scattering of cuprates is orders of magnitude smaller than the one observed in ordinary CDW materials (δn δ∆).…”
supporting
confidence: 92%
“…Im [ ( , )]. In the presence of weak time-independent scatterers its Fourier transform is given by [18,[37][38][39][40][41]…”
Section: Stm: Theory and Experimentsmentioning
confidence: 99%